THE IMPORTANCE OF IMMUNE INFLAMMATION IN THE DEVELOPMENT OF SENILE AORTIC STENOSIS - Numonova Guzaloy Davronbek kizi; Khujamberdiev M.A.; Usmonova Dilorom Ne'matjonovna (Scholar Express Journals, 2024)
Calcific aortic stenosis is the most common organic valvular heart disease in the elderly. Its prevalence is steadily increasing in the general population worldwide. The most frequently discussed cause of this defect is subclinical inflammation, the signs of which are clearly visible when examining sections of altered aortic valves. At the same time, the study of classical inflammation biomarkers in older people faces certain difficulties in standardization of studies, qualitative assessment and predictive value of the detected changes, which is especially relevant for patients with this heart defect.
Keywords: Calcific aortic stenosis; method